Pengembangan Game Edukasi Snake Maze Berbasis Android sebagai Inovasi Pembelajaran pada Materi Aljabar - Rizka Yolanda Putri Hariyanti; Janet Trineke Manoy (Universitas Negeri Surabaya, 2026)
The rapid and significant development of technology has brought about changes in the world of education. One example of technology that is currently developing is the Android-based smartphone. Advanced features such as the Internet of Things (IoT) and Artificial Intelligence (AI) have made smartphones multifunctional tools used by people of all ages, such as students who use them in their daily lives to play games or as a source of information in the learning process. There is an educational innovation that leverages technological advancements: Android-based educational game media for mathematics learning. This study aims to describe the development process of an educational game media titled “Snake Maze” as an educational innovation for algebra content and to describe the development process's outcomes evaluated based on validity, practicality, and effectiveness criteria. This study uses the ADDIE development model, which consists of five stages: Analyze, Design, Develop, Implement, and Evaluate. In the analysis stage, needs analysis, curriculum analysis, and technology analysis were conducted. The design stage includes preparing educational game content, creating storyboards, developing teaching modules, designing pre-tests and post-tests, and research instruments. During the development stage, the educational game was created using Scratch and validated by media experts and subject matter experts. The implementation stage involved Class VII-A of MTs Raden Fatah Driyorejo. Finally, the evaluation stage was conducted to assess the educational game based on validity, practicality, and effectiveness. The results showed that the educational game met the validity criteria set by media experts and was highly valid according to subject matter experts. It also met the practicality criteria based on user response surveys and observation sheets, and achieved effectiveness criteria based on N-Gain scores from pre-test and post-test results. The educational game “Snake Maze” can be utilized as an innovative learning tool for algebra content.